Narrative Literature Review : The Role of Ethics in Business Information - Aprilia, Cindy (Data Science: Journal of Computing and Applied Informatics, 2024)
Abstract. This paper investigates the critical role of ethics in business information, highlighting the challenges posed by the rapid evolution of ICT, which can hardly be addressed by formal legislative responses. A narrative literature review has been conducted to study how computer ethics acts as guidance in addressing the ambiguities and "grey areas" encountered in this field. Through a detailed exploration of the definitions, importance, objectives, and dimensions of computer ethics, the study showcases real-life examples of ethical dilemmas in information rights, property rights, accountability, system quality, and quality of life. The paper concludes that integrating ethical considerations into business practices is essential for responsible and sustainable digital transformation and for filling the gaps where laws may still blur. Keyword: Computer Ethics, Business Information Technology, Digital Transformation, Ethical Dilemmas, ICT, Legal Ambiguities, Sustainable Digital Transformation. Abstrak. Karya tulis ini membahas mengenai peran daripada etika terhadap perkembangan bisnis terkait teknologi informasi, dengan menekankan terhadap tantangan yang dihadapi oleh bisnis terkait perubahan ICT yang sangat cepat, dan sulit terkejar oleh perubahan legalitas. Penelitian dengan tinjauan literatur naratif dilakukan untuk mempelajari bagaimana etika dapat memberikan tuntunan untuk menhadapi ambiguitas dan â€œarea abu-abuâ€ daripada penerapan teknologi didalam bisnis terkait teknologi informasi. Melalui eksplorasi terperinci mengenai definisi, kepentingan, tujuan, dan dimensi etika komputer, penelitian ini menampilkan contoh nyata dilema etika dalam hak informasi, hak milik, akuntabilitas, kualitas sistem, dan kualitas hidup. Karya tulis ini menyimpulkan bahwa mengintegrasikan pertimbangan etis ke dalam praktik bisnis sangat penting untuk transformasi digital yang bertanggung jawab dan berkelanjutan serta untuk mengisi kesenjangan di mana undang-undang masih kabur. Kata Kunci: Etika Komputer, Bisnis Teknologi dan Informasi, Transformasi Digital, Dilema Etika, ICT, Ambiguitas atas Legalitas, Transformasi Digital Berkelanjutan.